Legal Measures Relating to the Freedom of Speech and the Right to Personality Protection - Michal Maslen; Martin Solík (Communication Today, 2025)
The study focuses on the analysis of the constitutional and legal limits of the exercise of freedom of speech. This freedom forms one of the pillars of a democratic and legal state. However, the Constitution of the Slovak Republic and the Convention on the Protection of Human Rights and Fundamental Freedoms allow for its legitimate limitations. The authors therefore examine the limits of restrictions on freedom of expression under the conditions of Slovak legislation. The role of independence and autonomy of media are also emphasised, and a specific case demonstrates the interaction between the personality protection of a public figure and freedom of expression.